KONSEP DASAR DALAM SISTEM INFORMASI MANAJEMEN DALAM PENDIDIKAN - Colarika, Siti; Zahro, Fatimah Az (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2023)
Abstract : Management in education requires a system that stores various information needed in educational institutions. The system can be said to be a management information system. Management information systems in education have a very broad scope and are based on initial concepts such as systems, data, databases, and information presentation in an educational institution. This article aims to explain the basic concepts related to management information systems in education. This article uses descriptive qualitative and literature study methods by collecting various information from various references related to systems, system development, education systems, information, data, databases and the provision of educational data and information. The education system is a regular arrangement of activities and sub-systems that are interrelated with each other and correlated to achieve the desired educational goals. In the system there are two parts that should not conflict with each other, the difference only lies in the procedures for use and elements such as teachers, students, student guardians, principals, and the community. Furthermore, the system requires development that is useful as an improvement in achieving educational goals through stored data and information.